CHARACTERIZATION OF NANOCERAMIC COATING PROPERTIES - MOHD NOOR, SITI NURSYUKRIAH (IRC, 2018)
The project studied the effect of dispersion of nanoceramic particles on the characteristic of newly formulation advanced ceramic coating. The interlocking of binder with nanoceramic particles will affect the mechanical properties of nanoceramic coating. The objectives are to evaluate the dispersion of nanoceramic coating formulation, to assess the mechanical properties of nanoceramic coating with various dispersion pattern, and to analyse the performance of nanoceramic coating comparing with conventional paint. The project analysed by having samples with undefined dispersion of nanoceramic particle in a formulation. The dispersion of nanoceramic particle in the formulation need to be defined by a specific microscope called Scanning Electron Microscope. The samples tested with Impact Test, Adhesion Test, Heat Test and Immersion Test based on American Society for testing and Materials (ASTM) standard. The dispersion of nanoceramic particles resulted to be in cluster formed dispersion. The dispersion of nanoceramic particles in the formulation affect the coating behaviour during the tests. Based on PETRONAS Technical Standard (PTS), the nanoceramic coating cannot be applied in any PETRONAS plantation. The formulation of nanoceramic coating should upgraded the interlocking of nanoceramic particles with the binder.